2005
DOI: 10.1142/s0219635205001002
|View full text |Cite
|
Sign up to set email alerts
|

There Is Something Out There: Distal Attribution in Sensory Substitution, Twenty Years Later

Abstract: Sensory substitution constitutes an interesting domain of study to consider the philosopher's classical question of distal attribution: how we can distinguish between a sensation and the perception of an object that causes this sensation. We tested the hypothesis that distal attribution consists of three distinct components: an object, a perceptual space, and a coupling between subjects' movements and stimulation. We equipped sixty participants with a visual-to-auditory substitution device, without any informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 10 publications
2
76
0
4
Order By: Relevance
“…However, it appears that most of the participants were also mainly focused on the vibrations on their wrist (LI-1; GA 20), and many of them also "paid attention to the sound of the motors in order to find [their] way" (LI-14; GA 15). 2 This would seem to suggest that, in addition to having had an experience of external obstacles, most of the participants still retained some awareness of aspects pertaining to the functioning of the device itself.…”
Section: Table 1 Results Of Participant Experience Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…However, it appears that most of the participants were also mainly focused on the vibrations on their wrist (LI-1; GA 20), and many of them also "paid attention to the sound of the motors in order to find [their] way" (LI-14; GA 15). 2 This would seem to suggest that, in addition to having had an experience of external obstacles, most of the participants still retained some awareness of aspects pertaining to the functioning of the device itself.…”
Section: Table 1 Results Of Participant Experience Questionnairementioning
confidence: 99%
“…Previous work in this area has already shown the value of using minimal technological interfaces in the science of perception (e.g., [32], [5], [2]. The ET is an original contribution to this domain.…”
Section: Enactive Torch: a Minimal Enactive Interfacementioning
confidence: 99%
“…One device, the Vibe, is similar to the tactile systems in that it presents the whole field of view at once and relies on the natural localisation abilities of the ear by expressing horizontal (left/right) position by controlling the relative amplitude in each ear (Auvray, Hanneton, Lenay, & O'Regan, 2005). The vOICe (which forms the basis for this study and is described in more detail below) encodes horizontal position temporally; i.e.…”
Section: Sensory Substitutionmentioning
confidence: 99%
“…More recently, another project called TheVibe (Auvray et al, 2005;Durette et al, 2008;Hanneton et al, 2010) has been developed. With its default configuration, this system associates a specific tone to each region of the acquired image.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the trajectories of moving visual targets can be differentiated following a short training period (Ambard et al, 2015). These systems have proven useful for walking (Bologna et al, 2009a;Durette et al 2008), and they allow for the development of distal attribution (Auvray et al, 2005).…”
Section: Introductionmentioning
confidence: 99%